FLIPPING THE CLASSROOM IN THE EFL READING FOR ACADEMIC PURPOSE COURSE DURING COVID-19: BARRIERS AND BOOSTERS - Uran, Stefanus Igolois G. (LLT Journal: A Journal on Language and Language Teaching, 2022)
The Flipped Classroom model has been a debatable issue, especially due to its triumph in the new set during the current outbreak of Covid-19. This study attempts to assess the effectiveness and explore the barriers and boosters of an FC approach in the Reading for Academic Purpose course in a private university in NTT Province, Indonesia. Employing a mixed-method design, this study generated data from the pre-and post-test and students TOWS (Threat-Opportunity-Weakness-Strength) analysis. Two groups of fourth-semester students, comprising 35 in a Blended Learning setting and another 23 in a Flipped Classroom, were taught similar reading skills and tasks. The paired-samples t-test indicates both FC (p=0.030.05, d=-0.70, medium effect size) and BL (p=0.000.05, d=-1.06, large effect size) settings were statistically significant by comparison. The independent-samples t-test used to contrast their effectiveness shows no statistically significant difference between groups (t[56]=1.11, p=0.27, d=0.29, small effect size). Although FC students benefited equally from the learning process in BL, they gained a lower mean score than their counterparts. TOWS analysis requires more improvement in FC due to students’ resilience to change, inability to self-learning management, poor collaboration and communication, technological setbacks, technical issues, and other socio-environmental constraints.